The value of innovation: the interaction of competition, R&D and IP - Greenhalgh, C; Rogers, M (University of Oxford, 2004)
This paper analyses market valuations of UK companies using a new data set of their R&D and IP activities (1989-1999). In contrast to previous studies, the analysis is conducted at the sector level, where the sectors are based on the technological classification in Pavitt (1984). The first main result is that the valuation of R&D and IP varies substantially across these sectors. To explore these variations the paper links competitive conditions with the market valuation of innovation. Using profit persistence as a measure of competitive pressure, we find that the sectors that are the most competitive have the lowest market valuation of R&D. Furthermore, within the most competitive sector ('science based'), firms with larger market shares (an inverse indicator of competitive pressure) also have higher R&D valuations. Another important result is that, on average, firms that receive only UK patents tend to have no market premium. In direct contrast, patenting through the European Patent Office does raise market value, as does the registration of trade market in the UK.